Sensor Fusion for Fault Detection and Classification in Distributed Physical Processes - Sarkar, Soumalya; Sarkar, Soumik; Virani, Nurali; Ray, Asok; Yasar, Murat (Frontiers in Robotics and AI, 2014)
This paper proposes a feature extraction and fusion methodology to perform fault detection and classification in distributed physical processes generating heterogeneous data. The underlying concept is built upon a semantic framework for multi-sensor data interpretation using graphical models of Probabilistic Finite State Automata (PFSA). While the computational complexity is reduced by pruning the fused graphical model using an information-theoretic approach, the algorithms are developed to achieve high reliability via retaining the essential spatiotemporal characteristics of the physical processes. The concept has been validated on a simulation test bed of distributed shipboard auxiliary systems.